The Application of Multimedia Visualization Platform in Business Management from the Perspective of Supply Chain Management - Nuan Wang (Journal of Robotics)
At present, in the process of enterprise operation and development, the implementation of enterprise operation modernization is a necessary condition and an effective measure to raise the management level. With the aim to achieve such enterprise modernization, it is necessary to improve the management’s modernization ability by improving the modernization level of enterprises. Therefore, corporate executives should pay more attention to the construction of informatization and implement informatization through effective methods and measures to further improve management efficiency. It will note the concept and connotation of business management, analyze the significance of the multimedia visualization platform at the level of enterprise business supply chain, analyze the current business management of enterprises and put forward scientific coping strategies, cater to the social development situation, and constantly innovate the development path of enterprise network information and chemical business management; this will help related majors.